2018
DOI: 10.1177/1054773818779492
|View full text |Cite
|
Sign up to set email alerts
|

The Most and the Least Performed Self-Care Behaviors Among Patients With Heart Failure in Jordan

Abstract: Assessing self-care is important aspects among patients with heart failure. However, few studies were conducted to assess self-care among patients with heart failure in Jordan. Therefore, this study aimed to assess the most and the least performed maintenance self-care behaviors and to examine the relationship between maintenance self-care behaviors and selected sociodemographics. A cross-sectional design utilizing a convenience sample of 226 patients with heart failure was used. The maintenance self-care mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
1
11
1
1
Order By: Relevance
“…Indeed, many patients with HF may be hospitalized for other causes related to influenza virus and bacterial pneumonia. 30 The result regarding proper sodium intake in this study was not consistent with the results of previous studies conducted in Jordan, 29 Japan, 31 and Iran 32 which indicated that asking for a low-salt diet was a frequently performed lifestyle. Further research is needed to examine the cultural limitations that Korean food can have, such as the taste of low-sodium foods, diet preferences, and food preparation styles in Korea.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, many patients with HF may be hospitalized for other causes related to influenza virus and bacterial pneumonia. 30 The result regarding proper sodium intake in this study was not consistent with the results of previous studies conducted in Jordan, 29 Japan, 31 and Iran 32 which indicated that asking for a low-salt diet was a frequently performed lifestyle. Further research is needed to examine the cultural limitations that Korean food can have, such as the taste of low-sodium foods, diet preferences, and food preparation styles in Korea.…”
Section: Discussioncontrasting
confidence: 99%
“…Having pneumococcal vaccination, proper sodium intake, and performing regular exercise were the least performed lifestyle recommendations. This finding was similar to the findings obtained by Tawalbeh and colleagues, 29 who indicated that avoiding getting sick by having a vaccine was one of the least performed lifestyles among patients with HF. It seems that patients with HF have less information about the vaccine and its importance.…”
Section: Discussionsupporting
confidence: 91%
“…In their cross-sectional study of 226 Jordanians with heart failure, they found lower than expected heart failure self-maintenance (Tawalbeh et al, 2020). The sample reported high rates of asking for low salt items and exercising and low rates of trying to avoid getting sick and checking ankles for swelling (Tawalbeh et al, 2020). This study suggests several areas for nursing interventions particularly in helping persons with heart failure with chronic disease management, symptom recognition, and self-care.…”
mentioning
confidence: 98%
“…Self-care is essential in most chronic diseases. Tawalbeh and colleagues (2020) investigated self-care behaviors of Jordanians with heart failure. In their cross-sectional study of 226 Jordanians with heart failure, they found lower than expected heart failure self-maintenance (Tawalbeh et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation